A review on synthesis, characterization, and applications of nano zero valent iron (nZVI) for environmental remediation. Issue 5 (3rd March 2016) - Mukherjee, Ritika; Kumar, Rahul; Sinha, Alok; Lama, Yangdup; Saha, Amal Krishna
ABSTRACT: The recent spark in the interest for the usage of nano zero valent iron (nZVI) as a remediation tool for contaminated land and groundwater is mainly due to its higher reactivity in comparison to micro ZVI, cost effectiveness, and potential to treat a broad range of contaminants. The authors review the recent developments and approaches made on synthesis on nZVI, strucuture and characterization of nZVI, the challenges faced in the transport of nZVI in the subsurface environment, and the augmentation of the motility of nZVI. The effective use of nZVI in remediating organic pollutants (halogenated organic compounds, pharmaceutical waste, and azo dyes) and inorganic pollutants (Ni 2+, PO4 3−, Co 2+, Cu 2+ ) carried out in recent studies is discussed. The potential risks and limitations of this emerging nanotechnology are also addressed.